P61 Human factors training: an experience driven approach. (November 2018) - Harrison, Tracey; Robinson, David; Martin, Andrew; Blood, Michaela; Clegg, Eleanor
Abstract : Background: Human Factors affect individuals' performance and directly impacts upon patient safety. It has been identified that understanding on what supports or challenges the way we work can make a difference. Through exploration surrounding implications of error, safety cultures and procedures whilst also looking at communication methods adopted in the clinical setting allows learners to identify the human factors; errors and potential pragmatic approaches to overcome safety issues. Summary of work undertaken: We have developed a unique inter-disciplinary half day session featuring two video recordings of serious incidents (SI's) that have occurred within our organisation. We recognised that through filming these incidents we were able to highlight when failures surrounding human factors occurred. Through facilitated discussion we are able to promote reflective practice in our delegates allowing consideration for changes in future practice and sharing of experiences. Delegates are aware the cases are genuine which we believe enhances the learning. By examining these incidents we demonstrate our commitment as an organisation to be a continually learning organisation, which promotes our mission statement to provide the highest quality healthcare at all times. Summary of results: The course whilst still in its infancy has received some very positive feedback. Over the past two courses we have had a total of 28 delegates attending the session from a variety of specialities and job roles. We believe this multi-disciplinary approach to learning enables delegates to interact with colleagues in a safe learning environment. All of the delegates were able to identify at least two learning points they attained from the session. Out of the 28 delegates, 18 scored the session as 'excellent' with 9 scoring as 'very good'. In regards to the relevancy to their role and learning needs, 22 delegates scored this as 'strongly agree' with 6 scoring as 'agree'. Our aim after each session is a raised awareness of human factors to reduce the risk of incidents. Conclusion and recommendations: We aim to develop the session and encourage specialities to run sessions for staff within that particular department. We also aim to develop a core faculty to facilitate the sessions, by involving a wide variety of 'human factors' enthusiasts from a range of staff groups and specialities will allow wider discussions within the groups. Following on from this success we have a number of sessions booked for the forthcoming year and are also running bespoke sessions for specific areas upon request.